Think Yellow and Keep Green-Role of Sulfanes from Garlic in Agriculture - Awais Anwar; Emma Gould; Ryan Tinson; Murree Groom; Chris J. Hamilton (MDPI AG, 2016)
Reactive sulfur species from garlic have long been renowned for their health benefits and antimicrobial properties. In agriculture the subject matter is now gathering momentum in the search for new bio-pesticides to addressing emerging environmental concerns and tighter restrictions on the use of many conventional chemical pesticides. Although the precise modes of action of these garlic-derived bioactives is complex, recent research has provided a number of new insights that deepen our understanding of garlic-derived products, such as garlic extracts and oils. Herein, their activity against various crop-damaging pests is reviewed. In many cases, there seems to be a broad range of activity associated with the sulfur-containing compounds derived from Allium species, which manifests itself in diverse insecticidal, antifungal, and nematicidal activities. These activities open a new understanding to develop this natural chemistry as a "green pesticide".